Nilai-nilai Karakter dalam Buku Teks Sejarah SMA Kelas XI di SMAN 7 Banjarmasin - Melisa Prawitasari; Raihani Sawitri; Heri Susanto (Universitas Batanghari Jambi, 2022)
The history material books generally describe facts, such as the number of years, the actors' names, where it happened, and a basic description of the flow of events. The history material books can provide character value strengthening for students, seen from how the teacher can collaborate using the history material books and how to package the delivery of material given to students to realize the aims and objectives of the Ministry of Education and Culture. Education and Culture, one of which is the development of students' potential with character and strengthening the character of students. This study used the descriptive qualitative method. Data collection techniques in this study used interviews and document studies. Data analysis techniques in this study are content analysis techniques for the validity of the data using semantic validity and stability reliability. The result of this research is that the teacher can instill character values in SMA Class XI's history books at SMAN 7 Banjarmasin by using various lectures, discussions, watching movies, and giving assignments. In addition to the use of techniques, the application of the hidden curriculum is also carried out in the learning process, namely by providing responsibility and discipline in following each history learning process. Based on theÂ identification results, we can conclude that implementing the character values contained in the history textbooks of SMA Class XI at SMAN 7 Banjarmasin is the core value of history learning. These core values are about the spirit of nationalism, love for the homeland, responsibility, and discipline